The global health system: actors, norms, and expectations in transition. - Nicole A Szlezák; Barry R Bloom; Dean T Jamison; Gerald T Keusch; Catherine M Michaud; Suerie Moon; William C Clark (PLoS Medicine, 2010)
In the first in a series of four articles highlighting the changing nature of global health institutions, Nicole Szlezák and colleagues outline the origin and aim of the series.